THE TRANSLATION OF MAGIC IN THE TRANSLATED RIDDARASOGUR. - LUMMER, FELIX (Medium Aevum, 2022)
The article explores the influence of Old French literature on Old Norse ideas of magic, particularly focusing on translations of French romances and other works. It investigates how terms and concepts related to magic were understood and represented in both cultures. Topics include the vocabulary of magic in Old French sources, the influence of Latin and Greek roots on terminology, and the portrayal of magical practices in Old Norse literature compared to the original French texts.